Impaired Economy of Gait and Decreased Six-Minute Walk Distance in Parkinson's Disease - Leslie I. Katzel; Frederick M. Ivey; John D. Sorkin; Richard F. Macko; Barbara Smith; Lisa M. Shulman (Parkinson's Disease)
Changes in the biomechanics of gait may alter the energy requirements of walking in Parkinson's Disease (PD). This study investigated economy of gait during submaximal treadmill walking in 79 subjects with mild to moderate PD and the relationship between gait economy and 6-minute walk distance (6 MW). Oxygen consumption (VO2) at the self-selected treadmill walking speed averaged 64% of peak oxygen consumption (VO2 peak). Submaximal VO2 levels exceeded 70% of VO2 peak in 30% of the subjects. Overall the mean submaximal VO2 was 51% higher than VO2 levels expected for the speed and grade consistent with severe impairment in economy of gait. There was an inverse relationship between economy of gait and 6MW (r=−0.31, P<0.01) and with the self-selected walking speed (r=−0.35, P<0.01). Thus, the impairment in economy of gait and decreased physiologic reserve result in routine walking being performed at a high percentage of VO2 peak.